Model-based Assessment of Data Availability in Health Information Systems - Winter, A.; Strübing, A. (Methods of Information in Medicine, 2008)
Objectives: To introduce a formal definition of data availability as a contribution to trustworthiness of health information systems and to automatically detect respective weaknesses and propose solutions.Method: Specifying an ontology, based on enterprise functions and application systems of (health) information systems and closely linked to the Three-Layer Graph-Based Meta Model (3LGM2). Deriving appropriate measures and algorithms.Results: A formal definition for data availability is introduced and elucidated by an example. This concept is used e.g. to disclose missing communication links and to suggest solutions.Conclusions: Data availability is a necessary but not sufficient condition for trustworthiness of health information systems. If information management has a thorough description of the information system at its disposal, e.g. by using 3LGM2, the calculation of data availability does not need further efforts.
Keywords: Health information systems; hospital information systems; information management; architectural models; quality; data availability; trustworthiness